The Mediation Process, its Principles and Challenges in Georgia - Batiashvili, Irina (Alternative Dispute Resolution Yearbook, 2022)
Mediation is based on the interests of the parties and not on rights, and this feature makes it even more effective. In the mediation process, the disputing parties try to prove their truth and, consequently, try to reach a "fair decision" together. Mediation may not settle with consesus, but after this process the disputing parties will know more precisely the causes of the conflict, their own demands, they will be free from aggression and will concentrate on the desired outcome. The psychological-emotional basis is largely seen in the mediation process. The initiation and ongoing (progress) of the mediation process depends on the voluntariness of the disputing parties; however, a legitimate limitation of the principle of voluntariness should be considered the different rules for initiating and continuing the mediation process in collective disputes. The neutrality and impartiality of the mediator during the mediation process reinforces the factor of trust between the parties. Confidentiality in mediation forms trust between the parties and the mediators. When it becomes mandatory to disclose information protected by the principle of confidentiality, it is necessary to maintain a balance between the principle of confidentiality of mediation and the public interest.